Women's preferences for a new contraceptive under development: an exploratory study - Madden, Tessa; Cohen, Sarah Y.; Paul, Rachel; Hurley, Emily G.; Thomas, Michael A.; Pauletti, Giovanni (Frontiers in Global Women's Health, 2023)
Objective: Currently available contraceptive methods do not meet the needs of all users. We sought to explore preferences of potential end-users regarding an on-demand, non-hormonal female contraceptive currently under development, using a web-based survey. Study Design: We recruited respondents for an exploratory survey via web link on Amazon Mechanical Turk (MTurk). Individuals were eligible if they were 18-44 years of age, identified as cis-gender female, were English-speaking, not pregnant, and had used barrier contraception previously. Respondents provided demographic characteristics and a basic reproductive history. We then provided a brief description of the potential contraceptive. Respondents were asked about their interest in the proposed contraceptive and preferences for method attributes. Results: A total of 500 respondents completed the survey. Three-quarters of respondents were <35 years of age and 48.2% were currently using a barrier contraceptive method. Three-fourths of respondents (73.8%) expressed interest in using the contraceptive under development. The majority wanted the method to be small (≤2 inches), rod-shaped, and low cost (<5 per use). More than half (59.4%) said it was important to be able to use the method without partners’ knowledge. The most reported potential concerns were vaginal irritation (51.6%) and lack of effectiveness (46.4%). Sixty percent of respondents were confident they could use the method correctly. Discussion: Available contraceptive methods lack attributes preferred by some users. Development of new contraceptives frequently does not involve end-user input early in the development process. Individuals in this sample displayed interest in the proposed contraceptive and expressed preferences that can inform the further development of this method.